Some questions of methodology for conducting tests of radiation protection of armored objects - Dovbnya, A.N.; Starenky, V.P.; Goncharov, I.G.; Cherniavskіy, I.Y.; Anashkin, O.A.; Vlasenko, V.O.; Ovcharenko, K.S. (Вопросы атомной науки и техники, 2020)
The results of approbation of the methodology for laboratory testing a materials for armored objects radiation protection by determining their half-value layer for nuclear radiations, which are typical for the main situations of the radiation factor effect in modern conditions, are presented.